Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.4103/sni.sni_348_17
|View full text |Cite
|
Sign up to set email alerts
|

Multinodular and vacuolating neuronal tumor: A case report and literature review

Abstract: Background:Multinodular and vacuolated neuronal tumor (MVNT) is a benign neuronal tumor that is newly recognized as architectural appearance that may be related to ganglion cell tumors in 2016 World Health Organization Classification of Tumors of the Central Nervous System. Herein, we report a case of MVNT in a 60-year-old man with a thorough literature review.Case Description:A 60-year-old male was pointed out the presence of intracerebral neoplasm located in left frontal lobe by a comprehensive medical exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…First reported in 2013, MVNTs are sporadic benign brain tumors [ 1 , 3 , 6 ]. MVNTs have been associated with ganglion cell tumors found in the cortical white matter [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First reported in 2013, MVNTs are sporadic benign brain tumors [ 1 , 3 , 6 ]. MVNTs have been associated with ganglion cell tumors found in the cortical white matter [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, MVNT was classified by the World Health Organization Classification of Tumors of the Central Nervous System [ 2 ]. Most of the MVNT cases reported yet have been in middle-aged patients with neurological symptoms including headaches and seizures [ 3 - 6 ]. Surgical intervention is often indicated in MVNTs related to epileptic symptoms [ 3 - 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent report, however, described that epilepsy was found in only 8 of 33 cases of MVNT confirmed pathologically or suspected by MRI (Nunes et al, 2017). A recent case study presented a pathologically confirmed MVNT without any neurological symptoms (Shitara et al, 2018). The authors argued that MVNT may be a “leave me alone” lesion and that it does not necessarily require invasive evaluation and treatment; it is mostly asymptomatic and does not manifest enlargement during its clinical course (Nunes et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Multinodular and vacuolating neuronal tumors have been reported to display highly suggestive imaging features, especially on magnetic resonance imaging (MRI) [3‐13]. An MVNT consists of the coalescence of small T2‐weighted imaging and fluid‐attenuated inversion recovery (FLAIR) hyperintense nodules in subcortical and juxtacortical areas, with rare or no post‐contrast enhancement.…”
Section: Introductionmentioning
confidence: 99%